DEPRESSION, ANXIETY, AND STRESS IN FAMILIES CARING FOR PERSONS WITH MENTAL DISORDERS - Perdana Febryanto, Kaldera Yugi; Rindayati, Rindayati; Supriati, Lilik; Harianto, Susilo; Iswatun, Iswatun; Okviasanti, Fanni (Universitas Airlangga, 2025)
Introduction: Mental disorders can disrupt the psychological, emotional, and social functioning of individuals, manifesting through symptoms such as hallucinations, delusions, and decreased motivation. These conditions can affect the families who care for them, often leading to depression, anxiety, and stress. Objective to determine the levels of depression, anxiety, and stress among families caring for individuals with mental disorders. Methods: This quantitative descriptive study involved 75 families who cared for individuals with mental disorders and met predetermined inclusion criteria. The research was conducted in the Manyar Sub-district Health Center area, Gresik Regency, in March 2022. A total of 63 respondents were selected using a purposive sampling method. Data were collected through questionnaires administered during home visits. The variables of depression, anxiety, and stress were measured using the Depression Anxiety Stress Scales (DASS). Results: The study revealed that 57% of families caring for members with mental disorders experienced mild levels of depression. The majority (60%) reported moderate levels of anxiety, while most families (78%) showed normal levels of stress. Conclusions: Most families caring for individuals with mental disorders experienced mild depression, moderate anxiety, and normal stress levels. Providing mental health education and relaxation training for family caregivers is important to reduce depression, anxiety, and stress, thereby improving the quality of care.